If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 7(7m + 9) = 0 Reorder the terms: 6m + 7(9 + 7m) = 0 6m + (9 * 7 + 7m * 7) = 0 6m + (63 + 49m) = 0 Reorder the terms: 63 + 6m + 49m = 0 Combine like terms: 6m + 49m = 55m 63 + 55m = 0 Solving 63 + 55m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 55m = 0 + -63 Combine like terms: 63 + -63 = 0 0 + 55m = 0 + -63 55m = 0 + -63 Combine like terms: 0 + -63 = -63 55m = -63 Divide each side by '55'. m = -1.145454545 Simplifying m = -1.145454545
| 3x-3=9-x | | 14*k+16*k+88=163 | | 2r-8+4=5(r+1) | | 23+x=2-2x | | 3(2x-4)=2(x-2) | | 3(1+4m)+5m= | | 5(x-2)=4(x-3) | | 1-x=x-1 | | 5-x=x-4 | | 3-5x=4x-6 | | 2*c+6*c+8=32 | | 2x-4=11-x | | 6x-4-2x=4 | | 9*y-5*y=8 | | 9-6x=2x+25 | | 2-5x=x-1 | | 3-4x=x-7 | | 6x^23+20=0 | | 4(3x+5)=5(2x+3) | | 32=13-4*x+21 | | 6w-15=9qw | | 4(x*5)+2=x+3 | | 5x-2=14-x | | 5x^2+34x+24=0 | | (13+x)+(9+x)=(73+x) | | x+17=39 | | 122-4x=32x+22 | | 9-8x=73-22x | | -130-7x=10x+23 | | 5x+7=-53-7x | | -4=8+6p | | =8wx*4w |